2014
DOI: 10.1002/2014tc003651
|View full text |Cite
|
Sign up to set email alerts
|

Transition from a singly vergent to doubly vergent wedge in a young orogen: The Greater Caucasus

Abstract: The Greater Caucasus Mountains, due to their youth (~5 Ma), provide an opportunity for insight into the early stages of orogen development during continent-continent collision. However, their recent tectonic evolution and first-order architecture remain unclear. Here we investigate the evolution of the orogen by integrating new observations of the fluvial geomorphology and neotectonics of the range with prior work on seismicity, geodetic strain, bedrock geology, and foreland basin structure. We find that the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
168
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 94 publications
(195 citation statements)
references
References 149 publications
(297 reference statements)
14
168
1
Order By: Relevance
“…1, Allen et al, 2004). The majority of active shortening structures within the GC are along the margins of the range and within the forelands but the interior of the GC is still experiencing active uplift (Avdeev and Niemi, 2011;Forte et al, 2014;Mosar et al, 2010).…”
Section: Tectonic Settingmentioning
confidence: 99%
See 3 more Smart Citations
“…1, Allen et al, 2004). The majority of active shortening structures within the GC are along the margins of the range and within the forelands but the interior of the GC is still experiencing active uplift (Avdeev and Niemi, 2011;Forte et al, 2014;Mosar et al, 2010).…”
Section: Tectonic Settingmentioning
confidence: 99%
“…Major structural systems of the region. Greater Caucasus structure is from Forte et al (2014) and Lesser Caucasus, Eastern Pontide, and Eastern Anatolia structures are from Dhont and Chorowicz (2006) and Koçyigit et al (2001). (For interpretation of the references to color in this figure, the reader is referred to the web version of this article.)…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lozar & Polino 1997;Adamia et al 2011) draw similar conclusions, and abundant evidence exists that Crimea experienced Eocene, then Oligocene, uplift (Panek et al 2009;Nikishin et al 2017). Conversely, Avdeev & Niemi (2011), Forte et al (2014 and Cowgill et al (2016) have suggested that the major phase of uplift occurred no earlier than c. 5 myr ago, whereas Rolland (2017) prefers a Miocene (c. 15 Ma) age for the onset of Caucasus uplift, based on geodynamic context and fission-track constraints on 'hard' Arabia-Eurasia collision (e.g. Okay et al 2010).…”
Section: Et Al 2000)mentioning
confidence: 82%